Local and systemic humoral immune response in farmed Atlantic salmon (Salmo salar L.) under a natural amoebic gill disease outbreak. Issue 66 (July 2017) - Marcos-López, Mar; Espinosa Ruiz, Cristóbal; Rodger, Hamish D.; O'Connor, Ian; MacCarthy, Eugene; Esteban, M. Ángeles
Abstract: Amoebic gill disease (AGD), caused by the protozoan parasite Neoparamoeba perurans, is one of the most significant infectious diseases for Atlantic salmon ( Salmo salar L.) mariculture. The present study investigated the humoral immune response (both local in gill mucus and systemic in serum) of farmed Atlantic salmon naturally infected with N. perurans in commercial sea pens, at two different stages of the disease and after freshwater treatment. Parameters analysed included activity of immune related enzymes (i.e. lysozyme, peroxidase, protease, anti-protease, esterase, alkaline phosphatase), IgM levels, and the terminal carbohydrate profile in the gill mucus. Overall, greater variations between groups were noted in the immune parameters determined in gill mucus than the equivalent in the serum. In gill mucus, IgM levels and peroxidase, lysozyme, esterase and protease activities were decreased in fish showing longer exposure time to the infection and higher disease severity, then showed a sequential increase after treatment. Results obtained highlight the capacity of gills to elicit a local response to the infection, indicate an impaired immune response at the later stages of the disease, and show partial reestablishment of the host immune status after freshwater treatment. In addition to providing data on the humoral response to AGD, this study increases knowledge on gill mucosal humoral immunity, since some of the parameters were analysed for the first time in gill mucus. Highlights: Longitudinal field case study undertaken in a commercial Atlantic salmon farm. Humoral immunity in gill mucus and serum during amoebic gill disease outbreak. Local response to the infection in gill mucus. Decreased response in gill mucus at the later stages of the infection. Partial restoration of the immune response in gill mucus post freshwater treatment.